TERRITORIAL CONSUMPTION MODELS - URBAN SPRAWL - (UN)SUSTAINABILITY: TIME FOR ANTI SPRAWL? - Zsuzsanna Váradi; Szilvia Kovács (European Regional Science Association (ERSA), 2011)
The presentation deals with a current urbanization phenomenon in Hungary, and highlights the cause-effect relationship of urbanization from interdisciplinary aspect and underlines the weakspots of sustainable urban development. After the Transition in 1990 the patterns of the settlement system were radically changed in Hungary too, which were transferred mainly the new urbanization trends, especially the suburbanization processes. The spreading of the urban areas and agglomerations started a new stage of territorial consumption. Based on the international and Hungarian literature it is well known, that more and more people moved out from the cities to live outside, but their working places, schools, their everyday life, their consumption and social contacts are realised in the cities. They `territorial consumption' is increasing in the outside, so the spreading of the suburban settlements is doubtless, but the inhabitants' everyday-life consumption take place in the cities, which usually caused sustainability problems and social, political and institutional conflicts as well, between the core cities and the surrounding settlements. The most visible problems of the phenomenon could be seen at the transport problems, at the service gaps and at the ecological problems. In order to link these aspects, the presentation focuses on the socially, economically and territorially defined consumption in the Budapest Metropolitan Region. It highlights the characteristic usage of urban space by several specified social groups, with the methods of empirical analysis . Firstly it would like to underline the main features and models of everyday life activities by localizing their consumption scenes, such as places of work, education and shopping. It would like to present the consequences of the new regional social structure and the reorganisation of the territorial consumption habits together, their dependence on each other, and the local or global consumption patterns of the different social groups. In addition, the lecture shows the consumer locations of public service and space among the different groups: it discusses the utilization of various urban public spaces and public institutions, the social infrastructure of the different social and territorial groups and the determining factors of these public consumer habits territorially.
Keywords: 330